Whole Genome Sequence and Development of a Transposon Mutagenesis System for Pseudomonas Putida sp.12 - Alyaa Abdelhameed1 , Rana Hussein Naser2 , Ansam Dawod Salman3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Nowadays, Heavy metal pollution is one of the most important environmental problems. All metals occurring in the biosphere originated in the earth’s crust; however, the toxic metal pollution of the biosphere has intensified rapidly since the onset of the industrial revolution, posing major environmental and health problems. Several studies have demonstrated the effect of metals on microbial diversity, biomass and activity. It is believed that metal Microbial activity is responsible for the bioremediation of the third elements in the periodic table. Selenium is an important trace element that required for in trace amounts for growth and metabolism but toxic at elevated concentration. The ability of a single mutant Pseudomonas putida sp.12(mariner transposon) has been used to search for genes involved in the biotransformation of selenite to red elemental selenium. This study aims to develop a transposon mutagenesis system for the model P. putida sp.12 to investigate the gene(s) that involved in selenite reduction. The conjugative plasmid pSAM_R1 containing the mariner transposon was used for transposon mutagenesis. A single mutant reliably impaired in selenite transformation, found that the mutant clones, contained an inactivation within pmoB, one of two copies of the gene encoding the largest subunit of particulate selenite-reduction. Physiological analysis of this “white mutant” indicated that the selenite-reducing activity, which was located primarily in the cytoplasm of the cells, could be rescued by adding format as an alternative source of electrons